(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder requiring lifelong pharmacotherapy and lifestyle modifications. Despite the availability of effective therapies, poor medication adherence remains a significant barrier to achieving optimal glycemic control, leading to increased morbidity, mortality, and healthcare costs. Identifying the factors that influence adherence is crucial for developing effective interventions. Objective: To prospectively evaluate the factors affecting medication adherence in patients with T2DM. Methods: This prospective, observational study was conducted at the Department of Medicine of a tertiary care hospital. A total of 160 patients with T2DM on oral hypoglycemic agents for at least one year were enrolled. Baseline demographic, socioeconomic, and clinical data were collected. Medication adherence was assessed at baseline and at the 6-month follow-up using the validated Morisky Medication Adherence Scale (MMAS-8). Glycemic control was measured via HbA1c levels. Patients were categorized as having high, medium, or low adherence. Multivariate logistic regression analysis was performed to identify independent predictors of poor adherence. Results: Of the 160 enrolled patients, 152 completed the six-month follow-up (dropout rate: 5%). The mean age was 56.4 ± 11.2 years, with a slight male predominance (56.6%). At baseline, only 28.3% (n=43) of patients had high adherence. At the 6-month follow-up, the number of patients with high adherence had significantly declined to 23.0% (n=35) (p=0.03). Factors significantly associated with poor adherence on multivariate analysis included: the presence of depressive symptoms (AOR: 3.2, 95% CI: 1.6-6.4, p=0.001), a higher pill burden (>5 pills per day) (AOR: 2.8, 95% CI: 1.4-5.6, p=0.004), lower monthly family income (AOR: 2.1, 95% CI: 1.1-4.1, p=0.02), and the experience of medication-related side effects (AOR: 2.4, 95% CI: 1.2-4.8, p=0.01). There was a strong correlation between lower adherence scores and higher HbA1c levels at the 6-month follow-up (r = 0.62, p<0.001). Conclusion: The rate of medication non-adherence in T2DM patients is alarmingly high and tends to decline over time. Key modifiable factors such as depression, pill burden, and side effects were identified as independent predictors of poor adherence. A multidisciplinary approach involving psychological support, regimen simplification, and proactive side-effect management is essential to improve adherence and, consequently, clinical outcomes in this patient population.